Morphological Changes of Parotid Gland in Experimental Hyperlipidemia - Ioanna D. Daskala; Christina C. Tesseromatis (Hindawi Limited, 2011)
Objective. The aim of this study was to investigate the role of hyperlipidemia in the microstructure of parotid gland and its possible amelioration through statin treatment on Wistar rats. Methods. Forty Wistar rats (111.06±3.36 g) were divided into 4 groups (A1, A2 controls, B1, B2 experimental). Groups A1 and A2 consumed normal cereal rodents diet during the experimental hyperlipidemic mixture. The A2 and B2 were treated with simvastatin (Zocor) 40 mg/kg/daily p.o. for 3 months. Results. Total cholesterol, triglycerides, high density lipoproteins, and low density lipoproteins were increased in groups B1 and B2 while the parotid weight was decreased. The histological findings demonstrated changes in the parotid gland morphology of the B1 and B2, such as the presence of chronic inflammation, fibrosis, lipocytes, and foci of lymphocytic infiltration. Conclusions. The influence of statin tended to predominate over the chronic inflammation while the lipocytes were decreased and remodelling of the parotid's structure occurred.